CARU MAÑCA MEBAYANG-BAYANG GODEL BANG DI PURA DALEM KUNCI LINGKUNGAN BATUDAWA KELURAHAN TANJUNG KARANG KECAMATAN SEKARBELA KOTA MATARAM - I Made Kastawa (Arete, 2019)
AbstractThis study aims to study the upakara caru manca using red calf as bayang- bayang(ritual material) in the Dalem Kunci Batudawa Temple, Tanjung Karang Village, Sekar Bela Sub-District, Mataram City. This research was de- signed in qualitative descriptive research. The formulation of the problem of this study are:(1)    What is the form of upakara caru manca using red calf as bayang- bayang (ritual material) in Jaba Pura Dalem Kunci? (2) What is the function of upakara caru manca using red calf as bayang-bayang (ritual material) in the Jaba Pura Dalem Kunci? and (3) What is the meaning of upakara caru manca using red calf as bayang-bayang (ritual material) in Jaba Pura Dalem Kunci?The results of the study show that the shape of the upakara caru manca using red calf as bayang-bayang (ritual material) in the Jaba Pura Dalem Kunci,(a)    the shape of the symbol is the same as the upakara carumancasata, and is equipped with bones and head godel bang (red calf), (b) the process begins with plug in sanggar surya as pesaksi, mapepada, and caru worship which ends with ngelebar. The function of upakara caru manca using red calf as bayang-bayang (ritual material) on the Jaba Pura Dalem Kunci is (a) its religious function as a medium to connect itself with Ida Sang Hyang Widhi Wasa in its manifestation as Durga Mahesasura Mardini; (b) Social functions: as a medium of interaction and social communication both individually and internally in Hindu groups in Lombok. 3) The meaning of upakara caru manca using red calf as bayang-bayang (ritual material) in Jaba Pura Dalem Kunci are: (a) meaningful as an increase in religiosity (sradha and bhakti) of Hindus, and (b) Increasing social solidarity between the Mataram City Hindu. Keywords: caru mañca, shadowing, goddess bang, temple Dalem key